Defining the Binding Region in Factor H to Develop a Therapeutic Factor H-Fc Fusion Protein against Non-Typeable Haemophilus influenzae - Wong, Sandy M.; Shaughnessy, Jutamas; Ram, Sanjay; Akerley, Brian J. (Frontiers in Cellular and Infection Microbiology, 2016)
Non-typeable Haemophilus influenzae (NTHi) cause a range of illnesses including otitis media, sinusitis, and exacerbation of chronic obstructive pulmonary disease, infections that contribute to the problem of antibiotic resistance and are themselves often intractable to standard antibiotic treatment regimens. We investigated a strategy to exploit binding of the complement inhibitor Factor H (FH) to NTHi as a functional target for an immunotherapeutic containing the NTHi binding domain of FH fused to the Fc domain of IgG1. Chimeric proteins containing the regions that most FH-binding bacteria use to engage human FH, domains 6 and 7 (FH6,7/Fc) and/or 18 through 20 (FH18–20/Fc), were evaluated for binding to NTHi. FH6,7/Fc bound strongly to each of seven NTHi clinical isolates tested and efficiently promoted complement-mediated killing by normal human serum. FH18–20/Fc bound weakly to three of the strains but did not promote complement dependent killing. Outer-membrane protein P5 has been implicated in FH binding by NTHi, and FH6,7/Fc binding was greatly diminished in five of seven P5 deficient isogenic mutant strains tested, implicating an alternative FH binding protein in some strains. Binding of FH18–20/Fc was decreased in the P5 mutant of one strain. A murine model was used to evaluate potential therapeutic application of FH6,7/Fc. FH6,7/Fc efficiently promoted binding of C3 to NTHi exposed to mouse serum, and intranasal delivery of FH6,7/Fc resulted in significantly enhanced clearance of NTHi from the lung. Moreover, a P5 deficient mutant was attenuated for survival in the lung model, suggesting that escape mutants lacking P5 would be less likely to replace strains susceptible to FH6,7/Fc. These results provide evidence for the potential utility of FH6,7/Fc as a therapeutic against NTHi lung infection. FH binding is a common property of many respiratory tract pathogens and FH/Fc chimeras may represent promising alternative or adjunctive therapeutics against such infections, which are often polymicrobial.